2021
DOI: 10.1186/s12904-021-00826-y
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, for patients with late stage chronic obstructive pulmonary disease, of being cared for in specialized palliative care compared to hospital. A nationwide register study

Abstract: Background In early stage chronic obstructive pulmonary disease (COPD), dyspnea has been reported as the main symptom; but at the end of life, patients dying from COPD have a heavy symptom burden. Still, specialist palliative care is seldom offered to patients with COPD; they more often receive end of life care in hospitals. Furthermore, symptoms, symptom relief and care activities in the last week of life for COPD patients are rarely studied. The aim of this study was to compare patient and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 44 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…A study has reported that the patients in specialised palliative care have benefits compared with hospitals. 22 Even considering that the patients were cared for within specialised palliative care, the results show that there was a significant difference in reported pain, anxiety and confusion between HCPs and FMs.…”
Section: Discussionmentioning
confidence: 85%
“…A study has reported that the patients in specialised palliative care have benefits compared with hospitals. 22 Even considering that the patients were cared for within specialised palliative care, the results show that there was a significant difference in reported pain, anxiety and confusion between HCPs and FMs.…”
Section: Discussionmentioning
confidence: 85%
“…However, a growing body of evidence has shown PC in both interstitial lung disease (ILD) and chronic obstructive pulmonary disease (COPD) is associated with a reduced risk of hospital admissions, emergency room visits, and hospital duration [10 ▪ ,11 ▪▪ ,12 ▪▪ ,13]. Moreover, several studies highlight significant relief of dyspnea following PC [14,15], often the most burdensome symptom in this population [16]. A randomized controlled trial reported that PC moderated the progression of dyspnea in ILD patients, with those receiving PC experiencing a slower progression of dyspnea over 12 months compared to patients receiving usual care [17 ▪▪ ].…”
Section: Advanced Lung Diseasementioning
confidence: 99%
“…In a recent systematic review evaluating 8 studies (7 randomized control trials), Santos and Reis-Pina (2023) revealed that PC interventions improved breathlessness in patients with chronic respiratory disease [19 ▪▪ ]. Studies of other mixed nonmalignant populations (including COPD) have also demonstrated improvement in symptoms after PC intervention [14,15].…”
Section: Palliative Care Management Strategiesmentioning
confidence: 99%
“…Comorbidities arise at more advanced stages of the disease trajectory and include weight loss, which is occasionally associated with cachexia and heart failure, resulting in increased dyspnoea [ 6 ]. Depression, psychosocial distress and sleep difficulties are also prevalent and are linked to a lower quality of life and premature death [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, there has been an increasing interest in the need and provision of palliative care for COPD patients [ 9 ]. One source of concern is whether end-of-life (EoL) care is effectively implemented [ 8 ]. According to Braço Forte and Sousa [ 10 ], “the EoL of patients with COPD is associated with progressive deterioration, worse quality of life, social isolation and absence of symptom control.…”
Section: Introductionmentioning
confidence: 99%